A novel SOCS5/miR‐18/miR‐25 axis promotes tumorigenesis in liver cancer. Issue 2 (9th November 2018) - Sanchez‐Mejias, Avencia; Kwon, Junsu; Chew, Xiao Hong; Siemens, Angela; Sohn, Hye Seon; Jing, Guo; Zhang, Bin; Yang, Henry; Tay, Yvonne
Abstract : The role of miRNAs with tumor suppressive activity in liver cancer has been well studied. However, little is known about potential oncomiRs in HCC. In our study, we conducted a systematic evaluation of candidate oncomiRs and found that upregulation of miR‐18a and miR‐25 in HCC was associated with poor patient survival and promoted proliferation in HCC cell lines. These two miRNAs belong to the polycistronic paralogous miR‐17‐92 and miR‐25‐106b clusters respectively. Although the members of both clusters are often upregulated in HCC, the contribution of individual miRNAs in these clusters to HCC tumorigenesis is not fully understood. We validated SOCS5 as a bona fide target of both miRNAs, and established, for the first time, the tumor suppressive role of SOCS5 in liver cancer. We further investigated the mechanism by which SOCS5 contributes to tumorigenesis, demonstrated that this SOCS5/miR‐18a/miR‐25 axis regulates the tumor suppressor TSC1 and downstream mTOR signaling, and highlighted the potential therapeutic use of miR‐18a and miR‐25 inhibition in restoring SOCS5 levels in HCC. Abstract : What's new? Little is known about the role of potential oncogenic miRNAs in liver cancer. This study found that upregulation of miR‐18a and miR‐25 in hepatocellular carcinoma (HCC) was associated with poor patient survival and promoted proliferation in HCC cell lines. Suppressor of cytokine signaling 5 (SOCS5) was identified as a bona fide target of both miR‐18a and miR‐25, and SOCS5 tumor suppressive role was established in liver cancer for the first time. The SOCS5/miR‐18a/miR‐25 axis was shown to regulate the tumor suppressor TSC1 and downstream mTOR signaling. miR‐18a and miR‐25 inhibition may be therapeutically valuable in restoring SOCS5 levels in HCC.